Ibn Taimiya dan Pemikiran Kalam Mengenai Sifat Tuhan - Muslim Nasution (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 1999)
This article seeks to introduce Ibn Taymiyyah and his theological thought, particularly concerning the attributes of God. Why emphasize the attributes of God? In response, within the discourse of theological reasoning (kalam), discussions about God are one of the most extensively debated themes, central to the issues of theological discourse.